2004
DOI: 10.1177/096739110401200102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing on Ductility and Strength of Kevlar/Polyethylene Composites

Abstract: Polymerization-filled composites (PFC) and melt-blended composites (MBC) were prepared to compare their mechanical properties. Improved ductility was obtained for PFC resulting from better fiber-polymer interfacial adhesion. On the other hand, ductility decreased upon increasing fiber content and strain rate, while normalized strengths were almost unchanged. This indicates that matrix and composites have similar responses to strain rate. Tensile strengths were compared with several modified models to include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The improvement of the characteristics of denture base materials is focused mainly on the mechanical properties and among them on fracture strength. Fractures in composites depend on the heterogeneity, interfacial adhesion between the materials' components, type of fracture and on the brittle or ductile nature of the components [8]. Zhang found that the higher the tensile strain and added fiber concentration the lower the ductility, while a higher break strain is linked to a higher ductility in the studied composites.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The improvement of the characteristics of denture base materials is focused mainly on the mechanical properties and among them on fracture strength. Fractures in composites depend on the heterogeneity, interfacial adhesion between the materials' components, type of fracture and on the brittle or ductile nature of the components [8]. Zhang found that the higher the tensile strain and added fiber concentration the lower the ductility, while a higher break strain is linked to a higher ductility in the studied composites.…”
Section: Introductionmentioning
confidence: 85%
“…Ductility was assessed by determining the fracture stress and strain values. For an unnotched tensile bar, energy to break is related to the area under a stress-strain curve [8]. Modulus of resilience was calculated after determining the flexural strength and the modulus of elasticity using the formula R=F 2 /2E, where R is the modulus of resilience, F is the flexural strength and E is the modulus of elasticity.…”
Section: Methodsmentioning
confidence: 99%